Cell wall fractions from Paracoccidioides brasiliensis induce hypergammaglobulinemia - Oliveira, Silvio Luis de [UNESP]; Silva, Marcelo Fernandes da [UNESP]; Soares, Angela Maria Victoriano de Campos [UNESP]; Silva, Celio Lopes (Springer Nature, 1993)
The antibody response against the antigen sheep red blood cells (SRBC) was investigated in mice pre-treated with formalin-killed Paracoccidioides brasiliensis or with cell wall fractions of the fungus. Pre-treatment with P. brasiliensis, as well as with the F1 fraction and beta-glucan significantly increased the anti-SRBC antibody response in the experimental groups as compared to the control group that received only SRBC. This immunomodulatory effect varied with the different doses employed and with pre-treatment time. We conclude that the cell wall fractions of P. brasiliensis might play an important role in the hypergammaglobulinemia associated with Paracoccidioidomycosis. © 1993 Kluwer Academic Publishers.
Keywords: Beta-glucan; Cell wall; Hypergammaglobulinemia; Paracoccidioides brasiliensis; Paracoccidioidomycosis